Vestibular and balance dysfunction in children with congenital CMV: a systematic review. Issue 6 (11th May 2022) - Shears, Annalie; Yan, Georgina; Mortimer, Harriet; Cross, Elizabeth; Sapuan, Shari; Kadambari, Seilesh; Luck, Suzanne; Heath, Paul T; Walter, Simone; Fidler, Katy J
Abstract : Objective: This systematic review evaluates vestibular and balance dysfunction in children with congenital cytomegalovirus (cCMV), makes recommendations for clinical practice and informs future research priorities. Design: MEDLINE, Embase, EMCARE, BMJ Best Practice, Cochrane Library, DynaMed Plus and UpToDate were searched from inception to 20 March 2021 and graded according to Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) criteria. Patients: Children with cCMV diagnosed within 3 weeks of life from either blood, saliva and/or urine (using either PCR or culture). Intervention: Studies of vestibular function and/or balance assessments. Main outcome measures: Vestibular function and balance. Results: 1371 studies were identified, and subsequently 16 observational studies were eligible for analysis, leading to an overall cohort of 600 children with cCMV. All studies were of low/moderate quality. In 12/16 studies, vestibular function tests were performed. 10/12 reported vestibular dysfunction in ≥40% of children with cCMV. Three studies compared outcomes for children with symptomatic or asymptomatic cCMV at birth; vestibular dysfunction was more frequently reported in children with symptomatic (22%–60%), than asymptomatic cCMV (0%–12.5%). Two studies found that vestibular function deteriorated over time: one in children (mean age 7.2 months) over 10 months and the other (mean age 34.7 months) over 26 months. Conclusions: Vestibular dysfunction is found in children with symptomatic and asymptomatic cCMV and in those with and without hearing loss. Audiovestibular assessments should be performed as part of neurodevelopmental follow-up in children with cCMV. Case–controlled longitudinal studies are required to more precisely characterise vestibular dysfunction and help determine the efficacy of early supportive interventions. PROSPERO registration: CRD42019131656. Abstract : This systematic literature review found congenital infection with cytomegalovirus (cCMV) to be associated with vestibular dysfunction in both symptomatic and asymptomatic children, with and without hearing loss. This highlights the importance of audiovestibular assessments when following-up children with cCMV.